PRESERVATION OF SARDINELLA LONGICEPS IN ICED AND CHILLED SEA WATER PART I- CHANGES DURING STORAGE WITH PARTICULAR REFERENCE TO BACTERIAL LOAD AND NITROGENOUS COMPOUND - KRISHNAKUMAR, S; HIREMATH, G G; MENON, N R (Fishery Technology, 2017)
Oil sardines in prime condition were subjected to onboard chHling; Two lots were chilled in CSW (samples C and Cl), a third lot was chilled in crushed ice (sample I) and a fourth lot left uniced on deck (Sample AI). Upon landing sample AI was iced and sample CI was removed from the CSW and iced. All the four samples were kept in a chilled room for storage studies. The fish chilled and stored in CSW rec?rd d the least, and the fish subjected to delayed icing, the highest values for all the 1ces of spoilage namely, free amino nitrogen, trimethylamine (TMA) and total volatile Â nitrogen (TVBN). The total psychrophilic bacterial number also showed a s1mtlar trend. The organoleptic assessment of the cooked samples revealed C I,CI, AI to be the order of preference throughout the storage. This assessment was found tc holdgood for the rest of the parameters as well. The CSW held fishes were found to be distinctly superior to the iced ones for the first five days of storage. Such a marked prevalence in quality for five days would suffice for the fish to fetch a premmm m the_ market over other landings of the same fish whether chilled or unchilled .._Chilhngonboard in CSW and icing the same after landings, did not show encouragmg results.